Hepatitis Disease Diagnosis Expert System Using Certainty Factor Method: Hepatitis Disease Diagnosis Expert System Using Certainty Factor Method - Sitorus, Dina Suzzete; Desiani, Anita (Universitas Ngudi Waluyo, 2024)
The liver is the largest visceral organ in the body with important roles such as hormone production, immunity, protein metabolism, and more. This visceral organ can also be affected by various diseases such as hepatitis. Hepatitis is an inflammatory disease of the liver caused by a virus. Hepatitis has five types of disease, namely Hepatitis A, Hepatitis B, Hepatitis C, Hepatitis D, and Hepatitis E. The types of hepatitis that have the most cases in Indonesia are Hepatitis A, Hepatitis B, and Hepatitis C. Hepatitis occurs due to a sedentary lifestyle. Hepatitis occurs due to unhealthy lifestyles and delays in treatment due to the patient's lack of knowledge about hepatitis. If hepatitis is not cured early, it can cause other diseases such as chronic liver and can also result in death, therefore this study aims to design an expert system that can diagnose hepatitis disease. This expert system design uses the certainty factor (CF) method. The certainty factor (CF) method is used because it can help and facilitate diagnosing hepatitis disease with a certainty value. The certainty value can be presented with a range of values from 0 to 100. This research produces an accuracy value of 80%, therefore this expert system is effective for measuring certainty in diagnosing hepatitis disease early.